2020
DOI: 10.3390/microorganisms8091425
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Bacteria Isolated from Different Aquatic Environments in the North of Spain and South of France

Abstract: Due to the global progress of antimicrobial resistance, the World Health Organization (WHO) published the list of the antibiotic-resistant “priority pathogens” in order to promote research and development of new antibiotics to the families of bacteria that cause severe and often deadly infections. In the framework of the One Health approach, the surveillance of these pathogens in different environments should be implemented in order to analyze their spread and the potential risk of transmission of antibiotic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
0
11
0
6
Order By: Relevance
“…They noticed that, among β-lactam-resistant ARB, almost all (97%) were confirmed to possess ESBL or pAmpC, and among pAmpC, all were detected as carrying the bla CMY-2 variant [ 116 ]. This variant, as well as others representing the CMY and DHA families, were detected in many other European studies of WWTPs from Germany [ 123 , 135 , 136 ], Romania [ 85 ], Sweden [ 96 , 109 ], Portugal [ 88 , 110 ], Poland [ 92 , 93 ], Slovakia [ 115 ], and Spain [ 188 ], as well as in studies conducted in Africa [ 127 ], North America [ 80 , 90 , 102 , 147 , 189 ], South America [ 87 ], and Asia [ 77 , 107 ]. Interestingly, Yim et al investigated samples for plasmid-mediated quinolone resistance genes from a WWTP in Canada and detected the presence of qnrB4-AmpC ( bla DHA-1 ) genes in plasmids among Citrobacter freundii isolates.…”
Section: Clinically Significant β-Lactam Resistance Genes In Wastewat...mentioning
confidence: 75%
“…They noticed that, among β-lactam-resistant ARB, almost all (97%) were confirmed to possess ESBL or pAmpC, and among pAmpC, all were detected as carrying the bla CMY-2 variant [ 116 ]. This variant, as well as others representing the CMY and DHA families, were detected in many other European studies of WWTPs from Germany [ 123 , 135 , 136 ], Romania [ 85 ], Sweden [ 96 , 109 ], Portugal [ 88 , 110 ], Poland [ 92 , 93 ], Slovakia [ 115 ], and Spain [ 188 ], as well as in studies conducted in Africa [ 127 ], North America [ 80 , 90 , 102 , 147 , 189 ], South America [ 87 ], and Asia [ 77 , 107 ]. Interestingly, Yim et al investigated samples for plasmid-mediated quinolone resistance genes from a WWTP in Canada and detected the presence of qnrB4-AmpC ( bla DHA-1 ) genes in plasmids among Citrobacter freundii isolates.…”
Section: Clinically Significant β-Lactam Resistance Genes In Wastewat...mentioning
confidence: 75%
“…In addition, two species of Salmonella are included, given their relationship with infections transmitted in the animal environment. Finally, antibiotic resistant bacteria isolated from different aquatic and farm environments from POCTEFA territory [ 41 ] and clinical origin completed the strain selection. All resistant strains were previously identified and characterized phenotypically and genotypically, to know the pattern of susceptibility to antimicrobials, the types of β-lactamase and the genes involved in resistance to methicillin ( mecA ), colistin ( mcr ) and vancomycin ( vanB ) [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, antibiotic resistant bacteria isolated from different aquatic and farm environments from POCTEFA territory [41] and clinical origin completed the strain selection. All resistant strains were previously identified and characterized phenotypically and genotypically, to know the pattern of susceptibility to antimicrobials, the types of β-lactamase and the genes involved in resistance to methicillin (mecA), colistin (mcr) and vancomycin (vanB) [41]. From the set of frozen strains (−80 • C) the working strains were prepared by spreading in general media (TSA; Scharlau, Sentmenat, Barcelona) and incubating at 37 • C for 24 h. The strains were kept refrigerated (5 • C ± 3 • C), making periodic passages to fresh media for the different tests (incubation at 37 • C for 24 h).…”
Section: Agar Well-diffusion Antibacterial Assaymentioning
confidence: 99%
“…The multidrug resistance of opportunistic pathogens causes major problems in the treatment of infections and thus poses a significant threat to morbidity and mortality worldwide [61]. Confirmation of the presence of multidrug-resistant bacterial strains in wastewaters has only strengthened the hypothesis that horizontal gene transfer may occur between the same and different bacterial species [66]. We found that neither the sampling environment nor the different sampling times affected the development of multidrug resistance in isolated bacterial strains in wastewater and then dam water (p > 0.05).…”
Section: Identification Of Bacterial Isolates and Evaluation Of Multidrug Resistancementioning
confidence: 99%